Semantic determination of SUPOSTO: The Theory of Predicative and Enunciative Operations point of view - Ferreira, Marly de Fátima (2022)
In this article, we aim to analyze utterances with occurrence of the supposed linguistic unit. Our aim is to apprehend the enunciative processes of their functioning, focusing on the role of constructing meaning and the semantic value that they stabilize. Thus, we are theoretically based on the Theory of Predicative and Enunciative Operations (TOPE), proposed by Antoine Culioli. It should be noted that TOPE is a theoretical and methodological work program. During the analysis we noticed the linguistic unit SUPOSTO (suposed) working as a gesture of doubt. Its presence in the process of construction of statements caused obstacles to the stabilization of values ​​according to the empirical of what it would be, for example: thief, sale, invasion and crime.